Reconfigurable on-chip communication link for efficient communication - S, Beulah Hemalatha; T, Vigneswaran (International Journal of Engineering and Technology, 2018)
Application specific reconfiguration of On-chip communication link is a fast growing research area in system on chip (SoC) based system design. Optimization of the communication link is important to achieve a trade-off between efficient communication and low power consumption. So achieving both efficient communication and low power consumption requires a special optimization mechanism. Such Optimization problems can be solved using a genetic algorithm. Here, in this paper genetic algorithm based On-chip communication link reconfiguration is presented. The algorithm will optimize efficiency of communication link with constrain of low power consumption. The parameters involved in power consumption and efficient communication link are coded in the chromosomes. By evolutionary iteration the optimal parameters of the communication link are derived that is used for the communication link successfully in the simulated system. The performance of the simulated system is analyzed which shows the out performance of the proposed system.